Impurity Profiling of Aspirin in Tablet Dosage Forms by Reverse Phase High Performance Liquid Chromatography - GOWRI SANKAR, D.; KONDAVENI, R.; RAGHAVA RAJU, T.V.; VAMSI KRISHNA , M. (Asian Journal of Chemistry, 2010)
An efficient reverse phase high performance liquid chromatographic (RP-HPLC) method was developed and validated for quantification of aspirin impurities which may coexist in bulk drugs and solid dosage forms. The separation was achieved on C18 column (100 mm × 4.6 mm, 5 μm) using a mobile phase of acetonitrile, isopropyl alcohol and sodium perchlorate. Flow rate was 1.5 mL/min. The photo diode array detector was operated at 275 nm. Forced degradation studies were performed on tablets powder which contain aspirin using acid hydrolysis, base, peroxide, water and UV, thermal, sunlight, humidity degradations. The method was validated for specificity, linearity, precision, accuracy and limit of quantification. The degree of linearity of the calibration curves, the recoveries of aspirin impurities, the limit of detection and quantification, for the HPLC method were determined. The method was found to be simple, specific, precise, accurate and reproducible. This method was applicable for the quality control of commercial aspirin tablets to quantify the drug and its related substances and to check the formulation content uniformity.